2015
DOI: 10.1111/jora.12230
|View full text |Cite
|
Sign up to set email alerts
|

Why Trust Matters: How Confidence in Leaders Transforms What Adolescents Gain From Youth Programs

Abstract: Youth's trust in program leaders is considered a key to the positive impact of youth programs. We sought to understand how trust influences youth's program experiences from their perspective. We interviewed 108 ethnically diverse youth (ages 12-19) participating in 13 arts, leadership, and technology programs. Analysis of these accounts suggested five ways in which youth's trust in leaders amplified program benefits. Trust increased youth's (1) confidence in leaders' guidance in program activities, (2) motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…This study was conducted within the Pathways Project (see Griffith & Larson, 2015;Larson, Izenstark, Rodriguez, & Perry, 2015; youthdev.illinois.edu), a longitudinal mixedmethods study on developmental processes within youth programs serving high-school-age youth, within the family context, and where the two contexts intersect. One of the main questions in the Pathways Project was "How do program leaders' interactions with youth facilitate youth's work and learning?"…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted within the Pathways Project (see Griffith & Larson, 2015;Larson, Izenstark, Rodriguez, & Perry, 2015; youthdev.illinois.edu), a longitudinal mixedmethods study on developmental processes within youth programs serving high-school-age youth, within the family context, and where the two contexts intersect. One of the main questions in the Pathways Project was "How do program leaders' interactions with youth facilitate youth's work and learning?"…”
Section: Methodsmentioning
confidence: 99%
“…Program participants value being able to trust youth program leaders (Halpern, Barker, & Mollard, 2000;Halpern, 2006;Hirsch et al, 2000;Hirsch, Deutsch, & DuBois, 2011;Strobel, Kirshner, O'Donoghue, & McLaughlin, 2008). Research suggests that an adolescent's trust in a program leader enhances the positive impact of experiences they have in the youth program context (Griffith & Larson, 2015). However, mentoring literature suggests forming trust in an adult and reaping the developmental benefits of that trust takes time (Rhodes, 2002).…”
Section: The Role Of Trust In Youth Program Contextsmentioning
confidence: 99%
“…These veteran leaders were using their authority not just to “balance” but to deliberately combine youth agency with restrained practitioner guidance and structure, as warranted. Leaders' judicious advice giving and limit setting were often aimed at providing the type of assistance that youth report is helpful: keeping their work on track, providing advice when needed, and helping youth feel safe in taking risks (Griffith & Larson, ; Kirshner, ). Youth doing projects are often heading into unfamiliar territory, attempting to achieve things they have not done before.…”
Section: Discussionmentioning
confidence: 99%
“…Youth report that they often appreciate leaders' selective use of their knowledge and authority to help with their projects. In three intensive interview studies (with data from 25 programs), youth reported benefiting from leaders' direction and assistance “when we need it,” for example, when leaders warned them that “ideas would not work,” kept them from getting in over their heads, and helped keep their work on track (Griffith & Larson, ; Kirshner, ; Larson & Angus, ). Yet youth are distrustful of adults who act unilaterally, without respect for their abilities and autonomy (Deutsch & Jones, ; Noam, Malti, & Karcher, ; Zeldin, Christens, & Powers, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strategic orientation, customer impact, market knowledge, commercial orientation, results orientation, change leadership, collaboration and influence, people and organizational development, and team development are the core competencies ruminated in this study. Strategic Orientation is the leader's ability to link long-range visions and concepts to daily work [53]. It implies the ability to think conceptually and to "see the big picture".…”
Section: Core Competenciesmentioning
confidence: 99%